Cognitive risks of anticholinergics in the elderly. (April 2013) - Gerretsen, Philip; Pollock, Bruce G
Many drugs commonly prescribed to the elderly have anticholinergic properties. Due to the current clinical use of drugs with mild-to-modest anticholinergic activity, the clinical manifestations of anticholinergic toxicity are likely to be nonspecific (e.g., cognitive impairment) and reflect the effects of cumulative anticholinergic burden. Age-associated physiological and pharmacokinetic changes increase anticholinergic drug effects in later life. Those with cognitive impairment and neurodegeneration are particularly susceptible to anticholinergic toxicity. Recent findings suggest that chronic anticholinergic burden may hasten or contribute to a neurodegenerative process. APOE ε 4 carrier status may be a genetic risk factor for vulnerability to negative anticholinergic effects. There is no clinically available laboratory test to assess anticholinergic levels. Clinicians need to be cognizant of anticholinergic risks in later life. The use of clinical scales (e.g., Anticholinergic Drug Scale) and consensus guidelines (e.g., Revised Beers Criteria) may be helpful.